Expression of Cyclin D1 in Oral Squamous Cell Carcinoma - Malak Abdulrahman Seid Ahmed; Nazik Omer; Ahmed M. Suliman; Mona Ellaithi (Sudan Journal of Medical Sciences)
Background: Cyclin D1 expression regulates normal cell cycle. Its deregulation or overexpression may cause disruption in the normal cell cycle control and lead to cancer progression. In this study, we aimed to study the expression of cyclin D1 in oral squamous cell carcinoma (OSCC) and find its association with the different grades of oral tumors, if any.